Aesthetic Eyelid Measurements of "Beautiful People": Gender Differences and Application for Thyroid Eye Disease Patients. Issue 7 (July 2021) - Evans, Jacob A.; Shaheen, Mohammed S.; Clark, Thomas J. E.; Shriver, Erin M.
Abstract : Background: There remains a paucity of studies investigating measurements of periocular structures of people popularly seen as "beautiful." Such measurements may be helpful in establishing postoperative goals and measuring aesthetic outcomes. This study (1) identifies aesthetic measurements of the periocular structures in idealized celebrities, (2) determines gender differences in such measurements, and (3) compares these measurements to patients who underwent surgical repair of upper eyelid retraction associated with thyroid eye disease. Methods: Digital analysis of 38 celebrity photographs in People 's "Most Beautiful People" and "Sexiest Man Alive" was performed to measure image-derived (denoted with an "i") margin reflex distance (iMRD1), tarsal platform show (iTPS), brow fat span (iBFS), and iTPS:iBFS ratio. The same analysis was used for 35 women who underwent surgical repair for thyroid eye disease-related upper eyelid retraction. Results: Significant gender differences ( P < 0.05) were observed in celebrity metrics, with women having higher upper eyelids (longer iMRD1) (3.30 mm versus 2.50 mm), longer iTPS measurements (3.90 mm versus 2.50 mm), and larger iTPS:iBFS values (0.31 versus 0.20). Postoperative thyroid eye disease patients had significantly higher upper eyelids (longer iMRD1s) (4.80 mm versus 3.30 mm), longer iTPS (5.10 mm versus 3.90 mm), and larger iTPS:iBFS (0.37 versus 0.31) than celebrities. Conclusions: There are significant gender differences in the periocular metrics of "beautiful people." Optimal aesthetic outcomes may be more effectively obtained by achieving a preferred range of ratios than by relying on independent measurements. Although aesthetic outcomes are multi-factorial, measurements of "beautiful" people provide helpful guidelines to gauge aesthetic outcomes.